On convolution model for ultrasound echo signal processing - Ming Chen. (2013)
Systematic ultrasound signal processing and imaging require a model for the ultrasound echo signal so to extract the tissue information for image construction. Based on careful studies of the classical ultrasound acoustics and traditional convolution model and taking into account the echo effects arising from anatomical tissue properties, this paper proposes a new convolution model for the ultrasound pulse-echo process, which presents dominant terms under common practically feasible conditions of medical ultrasound. The proposed convolution model can provide an effective means for processing ultrasound echo signals and constructing images.